VISUALIZATION AND ANALYSIS OF DATA ON ILLITERATE POPULATION IN INDONESIAN PROVINCES USING GOOGLE DATA STUDIO - Tobias Duha; Hanifah Nurul Muthmainah; Gentur Wahyu Nyipto Wibowo; Susatyo Adhi Pramono; Rizki Dewantara (Jurnal Scientia, 2023)
This study examines the percentage of illiterate individuals in 34 Indonesian provinces in 2022. This data is analyzed by segregating the percentage of the illiterate population by age, specifically 15 years, 15-44 years, and 45 years and older. The analysis begins by examining the percentage of 15-year-olds who are illiterate. Significant disparities exist between provinces, with Papua province having the highest percentage (18.81%) and North Sulawesi province having the lowest percentage (0.19%). Visualization of the data as tables and maps plainly demonstrates this distinction. Next, the analysis examined the percentage of the 15-44-year-old population that was illiterate. Papua province has the greatest percentage, at 15.06%, while North Sulawesi and Riau provinces have the lowest percentage, at 0.07% each. This comparison is also clarified by means of data visualization. Finally, data regarding the percentage of illiterate individuals aged 45 and older were analyzed. Again, the province of Papua has the highest percentage at 28.35%, while the province of North Sulawesi has the lowest percentage at 0.34%. In addition to tables and maps, the results of this analysis are also presented in tabular format. This data provides a clear picture of the level of illiteracy in various Indonesian provinces in 2022, and the results can be used to devise more effective education programs and more targeted solutions to combat illiteracy in Indonesia.